High-Throughput Screening Identifies MicroRNAs Regulating Human PCSK9 and Hepatic Low-Density Lipoprotein Receptor Expression - van Solingen, Coen; Oldebeken, Scott R.; Salerno, Alessandro G.; Wanschel, Amarylis C. B. A.; Moore, Kathryn J. (Frontiers in Cardiovascular Medicine, 2021)
Investigations into the regulatory mechanisms controlling cholesterol homeostasis have proven fruitful in identifying LDL lowering therapies to reduce the risk of atherosclerotic cardiovascular disease. A major advance was the discovery of proprotein convertase subtilisin/kexin type 9 (PCSK9), a secreted protein that binds the LDL receptor (LDLR) on the cell surface and internalizes it for degradation thereby blunting its ability to take up circulating LDL. The discovery that loss-of-function mutations in PCSK9 lead to lower plasma levels of LDL cholesterol and protection from cardiovascular disease led to the therapeutic development of PCSK9 inhibitors at an unprecedented pace. However, there remain many gaps in our understanding of PCSK9 regulation and biology, including its post-transcriptional control by microRNAs. Using a high throughput human microRNA library screen, we identified microRNAs targeting the 3’ untranslated region of human PCSK9. The top 35 hits were confirmed by large format PCSK9-3’-UTR luciferase assays and 10 microRNAs were then selected for further validation in hepatic cells, including effects on PCSK9 secretion and LDLR cell surface expression. These studies identified seven novel microRNAs that reduce PCSK9 expression, including miR-221-5p, miR-342-5p, miR-363-5p, miR-609, miR-765 and miR-3165. Interestingly, several of these microRNAs were also found to target other genes involved in LDLR regulation, and potently upregulate LDLR cell surface expression in hepatic cells. Together, these data enhance our understanding of post-transcriptional regulators of PCSK9 and their potential for therapeutic manipulation of hepatic LDLR expression.